Mechanics of fresh, frozen-thawed and heated porcine liver tissue. (June 2014) - Wex, Cora; Stoll, Anke; Fröhlich, Marlen; Arndt, Susann; Lippert, Hans
Abstract Purpose: For a better understanding of the effects of thermally altered soft tissue, the biothermomechanics of these tissues need to be studied. Without the knowledge of the underlying physical processes and the parameters that can be controlled clinically, thermal treatment of cancerous hepatic tissue or the preservation of liver grafts are based primarily on trial and error. Materials and methods: Thus, this study is concerned with the investigation of the influence of temperature on the rheological properties and the histological properties of porcine liver. Results: Heating previously cooled porcine liver tissue above 40 °C leads to significant, irreversible stiffness changes observed in the amplitude sweep. The increase of the complex shear module of healthy porcine liver from room temperature to 70 °C is approximately 9-fold. Comparing the temperatures −20 °C and 20 °C, no significant difference of the mechanical properties was observed. Furthermore, there is a strong relation between the mechanical and histological properties of the porcine liver. Temperatures above 40 °C destroy the collagen matrix within the liver tissue. This results in the alteration of the biomechanical properties. The time-temperature superposition principle is applied to generate temperature-dependent shift factors that can be described by a two-part exponential function model with an inflection temperature of 45 °C. Conclusions: Tumor ablation techniques such as heating or freezing have a significant influence on the histology of liver tissue. However, only for temperatures above body temperature an influence on the mechanical properties of hepatic tissues was noticeable. Freezing up to −20 °C did not affect the liver mechanics.